Novel immunologic mechanisms in eosinophilic esophagitis. (October 2017) - Caldwell, Julie M; Paul, Misu; Rothenberg, Marc E
Highlights: Eosinophilic esophagitis (EoE) is a tissue-specific disease. EoE epithelium exhibits impaired barrier function and dysregulated differentiation. Innate and adaptive immunologic mechanisms drive EoE pathogenesis. Both genetic and environmental components influence EoE pathogenesis. Recently developed rational EoE therapies reduce esophageal eosinophilia.